Effects of adaptations of a phonics-based reading intervention program on reading and spelling skills of students with intellectual disability who require augmentative and alternative communication - Linder, Anne-Laure; Geyer, Megan; Atzemian, Myrto; Meuli, Natalina; Martinet, Catherine; de Chambrier, Anne-Françoise; Dessemontet, Rachel Sermier (Frontiers in Education, 2023)
This study is an examination of the effects of a series of adaptations made to a phonics-based reading intervention program for students with an intellectual disability (ID). The adaptations were designed to make the program more accessible to augmentative and alternative communication (AAC) users. They consisted of using a pointing-response modality to allow participants to give their answers as well as the use of internal speech, which involved performing certain tasks in one's head because students with complex communication needs could not perform them aloud. Participants also completed reading and spelling activities on an iPad® application. A multiple-probe-across-participants design was used. Specifically, the adapted reading program's effects were assessed on reading and spelling skills of three students with ID who were AAC users. The outcomes indicate that all three participants improved their reading skills, and two participants also improved their spelling skills. The results and implications for future research are discussed.